2022
DOI: 10.3390/ijerph19084700
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence Predicts Physical Activity Maintenance and Health-Related Quality of Life: A 3-Year Longitudinal Study on Cardiovascular Patients

Abstract: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality globally. A physically active lifestyle can improve the health-related quality of life (HRQoL) of people with CVD. Nevertheless, adherence to a physically active lifestyle is poor. This study examined the longitudinal (pre-event, 6-, 12-, 24-, and 36-month follow-ups) physical activity profiles in 275 patients (mean age = 57.1 years; SD = 7.87; 84% men) after the first acute coronary event. Moreover, it investigated the associations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
3
2
0
1
Order By: Relevance
“…The last finding regards the significant direct association observed between physical activity behavior and HRQoL, both evaluated at final follow-up. This result is consistent with prior research that already showed a significant impact of being regularly physically active on patients’ cardiovascular health (Adorni et al, 2022; Arija et al, 2018; Hawkes et al, 2013; Montayre et al, 2022). Notably, the present study adds complexity to this association by estimating significant indirect effects of baseline HRQoL and cardiac self-efficacy evaluated 18 months before.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The last finding regards the significant direct association observed between physical activity behavior and HRQoL, both evaluated at final follow-up. This result is consistent with prior research that already showed a significant impact of being regularly physically active on patients’ cardiovascular health (Adorni et al, 2022; Arija et al, 2018; Hawkes et al, 2013; Montayre et al, 2022). Notably, the present study adds complexity to this association by estimating significant indirect effects of baseline HRQoL and cardiac self-efficacy evaluated 18 months before.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, as described by prior works (Castillo-Mayén, Luque, Rubio, et al, 2021; Modica et al, 2019; Sandberg et al, 2015), functional coping strategies, affective balance, and stronger intention to adopt healthier behaviors were found determinant in achieving better cardiovascular health. Overall, this finding extends the current body of knowledge that already established strong relationships between positive psychological profiles and the adoption of healthier behaviors, and how these relations are longitudinally associated with better perceived cardiovascular health (Adorni et al, 2022; Castillo-Mayén, Luque, Rubio, et al, 2021; Roshanaei-Moghaddam et al, 2009). In addition to this, the present work not only sheds light on the indirect role of psychological and behavioral factors in the longitudinal improvement of HRQoL, but it may also provide future preventive intervention programs with crucial components to be targeted in order to enhance patients’ self-management skills following a cardiac event.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Daily physical activity. In other studies, engagement in PA after a cardiovascular event was correlated to coherence (42). In a recent study from 2020 on patients with multiple sclerosis, as in our survey, no associations were visible (43).…”
Section: Discussionsupporting
confidence: 55%
“…Además, se observa que las personas que realizan actividad física suficiente obtienen puntuaciones mayores en el SOC. Un estudio reciente ha identificado los factores que influyen en la adherencia en la actividad física sugiriendo el SOC como uno de estos factores (29).…”
Section: Discussionunclassified